2019
DOI: 10.25165/j.ijabe.20191205.4646
|View full text |Cite
|
Sign up to set email alerts
|

Range formula based on angle of dispersion and nozzle configuration from an impact sprinkler

Abstract: Jet breakup and dispersion from impact sprinkler are mainly influenced by the configurations of nozzle and dispersion device. Based on the structure, different types of nozzles were designed and tested with a pointed tip dispersion device under low pressure conditions. Experiments were performed using High-Speed Photographic technique, and Matlab computation program was established and applied to determine the initial jet breakup length and angle of dispersion from the nozzles. The sprinkler range decreased wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…7. The overall sight of the dispersion intensity of disintegrated ligaments and droplets from the jet surface, represented in the prevalence of contour line of 0.05 ALVF in the domain [50], [51], can be noted from Fig. 7.…”
Section: Average Contoursmentioning
confidence: 98%
“…7. The overall sight of the dispersion intensity of disintegrated ligaments and droplets from the jet surface, represented in the prevalence of contour line of 0.05 ALVF in the domain [50], [51], can be noted from Fig. 7.…”
Section: Average Contoursmentioning
confidence: 98%
“…There are 3 different criteria for defining the jet boundary as reported by Iyer and Abraham [49]. The criterion consistent with Jiang et al [50] was adopted in this work. The criterion states that the boundary is defined as the locus of points having a fixed low value of liquid volume fraction.…”
Section: Average Contoursmentioning
confidence: 99%
“…Currently, research on jet‐breaking characteristics is mainly carried out using experimental methods. The influence of an impact sprinkler NSWDD was studied by Jiang et al (2019), focusing on the crushing characteristics of the impinging jet under low pressure using high‐speed photography. It was found that the diffusion angle of the impinging jet gradually decreased with increasing jet velocity.…”
Section: Introductionmentioning
confidence: 99%